2002
DOI: 10.1124/jpet.102.041715
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cyclooxygenase (COX)-1 and COX-2 Inhibition in Nonsteroidal Anti-Inflammatory Drug-Induced Intestinal Damage in Rats: Relation to Various Pathogenic Events

Abstract: We recently reported that cyclooxygenase (COX)-2 expression was up-regulated in the rat small intestine after administration of indomethacin, and this may be a key to nonsteroidal antiinflammatory drug (NSAID)-induced intestinal damage. In the present study, we investigated the effect of inhibiting COX-1 or COX-2 on various intestinal events occurring in association with NSAID-induced intestinal damage. Rats without fasting were treated with indomethacin, SC-560 (a selective COX-1 inhibitor), rofecoxib (a sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
83
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 34 publications
11
83
0
Order By: Relevance
“…It has been suggested that GI toxicity arises when both COX-1 and COX-2 enzymes are inhibited, and that inhibiting either one alone does not cause injury to the gastrointestinal mucosa (Takeuchi et al, 2003;Tanaka et al, 2002aTanaka et al, , 2002b. Our data presented herein may align with this hypothesis, as rofecoxib did not induce an APR at 250-fold its presumptive efficacious dose (Riendeau et al, 2001).…”
Section: Drug Signatures For the Acute Phase Responsesupporting
confidence: 74%
“…It has been suggested that GI toxicity arises when both COX-1 and COX-2 enzymes are inhibited, and that inhibiting either one alone does not cause injury to the gastrointestinal mucosa (Takeuchi et al, 2003;Tanaka et al, 2002aTanaka et al, , 2002b. Our data presented herein may align with this hypothesis, as rofecoxib did not induce an APR at 250-fold its presumptive efficacious dose (Riendeau et al, 2001).…”
Section: Drug Signatures For the Acute Phase Responsesupporting
confidence: 74%
“…Oral administration of IM was performed as described previously (Tanaka et al, 2002). Briefly, wild-type (WT) and Atg5-conditional knockout (CKO) mice (n 5 5 to 6 for each) were given IM p.o.…”
Section: Methodsmentioning
confidence: 99%
“…7), which may be due to reciprocal induction of COX-2 as reported in rat small intestine. 47) In contrast, meloxicam treatment slightly but significantly augmented PGE 2 content in colon but not in small intestine. The implication of such differential COX-2 and prostaglandin responses in these abdominal organs to the modulation of zymosan-induced anorexic responses by these COX inhibitors are largely unknown.…”
Section: Discussionmentioning
confidence: 94%